Community Structure of the Bivalve in Tidung Island Waters, Seribu Islands Regency, DKI Jakarta Province - Harahap, Anugrah Setiadari; Nasution, Syafruddin; Efriyeldi, Efriyeldi (Fakultas Perikanan dan Kelautan Universitas Riau, 2023)
Community structure is a concept that studies the composition of species and abundance in a community. This research was conducted in April 2022 in the waters of Tidung Island, Seribu Islands Regency. The purpose by conducting this study was to determine the structure of the bivalve community which includes species, density, relative density, diversity, uniformity, dominance, distribution pattern and index of similarity. The research method used in this study is survey method, were carried out at 3 stations, station determination using purposive sampling method taking into account the anthropogenic conditions in the study area. Based on results, types of bivalves found consisted of 6 species of bivalve. The species most commonly found is Atrina pectinata. The abundance of bivalve obtained ranged from 2.67 – 5.47 ind/m2. The results of the ANOVA test between observation stations obtained the value of sig. <0.05, so it can be concluded that the density of Bivalvia between stations was significantly different, except for stations I and III. The distribution pattern of bivalves in the waters of Tidung Island is in groups. The value of the Diversity Index in the study area is classified as moderate (2.06 – 2.12). The uniformity index value during ranged from 0.80 – 0.82 wich is included in the balanced category. The dominance index between stations is different with a value range of 0.25 – 0.28 which means that no species dominates at each station.